PENINGKATAN HASIL BELAJAR LAY UP BOLABASKET MELALUI PENDEKATAN BERMAIN ONE-TWO STEP PADA SISWA KELAS VIII SMP NEGERI 9 SEMARANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve student learning outcomes in the following study lay up basketball in the eighth C grade students of SMP N 1 Semarang in 2013 through the medium of the game one-two step.This research is a class act. This study used 2 cycles, where each cycle consists of: 1) planning, 2) implementation of the action; 3) observation; 4) reflection. Research conducted includes three domains, namely the domain of psychomotor, affective, cognitive domain.The results showed that the learning outcomes lay up basketball game with the media one-two step in class VIII C 9 Semarang SMP N positive impact, as seen in the results of students' mastery learning which exceeds a predetermined KKM has increased by 75 in the first cycle in the form of completeness study reached 50%, while in the second cycle reached 88.46% mastery learning. It is concluded that learning the lay-up basketball game with the use of media one-two-step has a positive effect, which can improve student learning outcomes that can facilitate students to understand and perform langkahan lay up correctly.